The concept understanding of students in Mappi concerning fractional operation in the matriculation program 2018/2019 - Niluh Sulistyani; Cyrenia Novella Krisnamurti; Agata Galuh Puspita Putri (Math Didactic: Jurnal Pendidikan Matematika, 2020)
This study aims to analyze the understanding of the concept of the Fractions operations of Mappi students. This was qualitative research with the subject were 5 students from Mappi Regency, Papua in the Class A matriculation program. The study was conducted in February-May 2019. Data were obtained from written test results and were strengthened by interview results. Test results and interviews were analyzed descriptively and qualitatively. The results showed that the five students of Class A matriculation program had different concept understanding abilities. Subject 1 could understand the concepts of addition and subtraction in the fraction operation and changed the form of mixed fractions into ordinary fractions. Subject 2 could understand the concept of addition in fraction operations and change the form of mixed fractions into ordinary fractions. Subject 3 understands the concepts of addition and subtraction in fraction operations, which could represent and change the form of mixed fractions into ordinary fractions. Subject 4 could understand the concepts of addition and subtraction in the operation of fractions. Subject 5 had a low understanding of the concept and could only change the form of mixed fractions into ordinary fractions. With these results, the conceptual understanding of 5 Mappi students about fractional operations needs to be improved.